143k views
5 votes
Solving system by substitution

Solving system by substitution-example-1

1 Answer

1 vote

Answer:

The solution of this system is (9, 2).

Explanation:

Substitute x - 7 for 'y' in the first equation. We get:

x - 3(x - 7) = 3 Doing this temporarily eliminates the variable 'y'.

Now perform the indicated multiplication, and then combine like terms:

x - 3x + 21 = 3, or

-2x = -18

so that x = 9. Substituting 9 for x in the second equation, we get:

y = 9 - 7, or y = 2.

The solution of this system is (9, 2).

User Abest
by
4.8k points